Economic Implications of Alternative Publishing Models: Self-archiving and Repositories - Houghton, John W. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
A knowledge economy has been defined as one in which the generation and exploitation of knowledge has come to play the predominant part in the creation of wealth. It is not simply about pushing back the frontiers of knowledge; it is also about the more effective use and exploitation of all types of knowledge in all manner of economic activities. One key question is whether there are new opportunities and new models for scholarly publishing that might better serve researchers and more effectively communicate and disseminate research findings. Building on previous work, this paper looks at the costs and potential benefits of alternative models for scientific and scholarly publishing, describing the approach and methods used and summarising the findings of a study undertaken for JISC in the United Kingdom. It concludes that different publishing models can make a material difference to the costs faced by and benefits realised from research communication, and it seems likely that more open access would have substantial net benefits.